A qualitative study of active participation in sport and exercise for individuals with multiple sclerosis. (22nd April 2019) - Smith, Moira; Neibling, Bridee; Williams, Gavin; Birks, Melanie; Barker, Ruth
Abstract: Objective: The aim of this study was to explore the experience of participation in sport and exercise for individuals with multiple sclerosis (MS) with minimal disability. The objectives were to gain an understanding of key factors that influence participation in sport and exercise and to determine support required by individuals with MS to participate in their choice of sport and exercise for as long as possible. Methods: A qualitative, descriptive study utilizing three focus groups was conducted. Data were analysed thematically aided by NVivo software. Participants were individuals with MS who had an Expanded Disability Status Scale score of 0–4, indicating full ambulation. All participants were living in northern Queensland, Australia. Results: Sixteen individuals participated; 63% of whom regularly participated in sport or exercise. All participants viewed sport and exercise positively and identified inherent benefits of exercise. Five key themes emerged to describe the experience of participating in sport and exercise: "personally engaging with exercise, " "influencing barriers and enablers of exercise, " "sustaining independence, " "integrating exercise into lifestyle, " and "getting the balance right." Most participants felt that advice and guidance from health professionals about the optimum mode and dose (how much and how often) of exercise was lacking. Conclusions: Participation in sport and exercise was valued by individuals with MS with minimal disability for sustaining independence and an active lifestyle. Personalized exercise advice from health professionals was the key support identified by participants to assist them to maintain an active lifestyle for as long as possible.